1999
DOI: 10.1046/j.1442-2042.1999.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Transitional cell carcinoma of ureteral stump after radical nephrectomy for renal cell carcinoma

Abstract: A 68-year-old male presented with microscopic hematuria during a routine checkup after undergoing a radical nephrectomy for renal cell carcinoma. Retrograde ureterography demonstrated a ureteral stump tumor. The ureteral stump was completely resected with a bladder cuff and histologic diagnosis was grade 2 to 3 transitional cell carcinoma of the ureteral stump. He is doing well and has been tumor-free for 2 years. The ureteral stump must be correctly evaluated using retrograde ureterography in any patient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge only 11 cases, including our own, have been reported in the literature [1][2][3][4][5][6][7][8][9][10] as hydronephrosis, urinary calculi, or renal tuberculosis may be implicated in developing primary ureteral carcinomas [11].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To the best of our knowledge only 11 cases, including our own, have been reported in the literature [1][2][3][4][5][6][7][8][9][10] as hydronephrosis, urinary calculi, or renal tuberculosis may be implicated in developing primary ureteral carcinomas [11].…”
Section: Discussionmentioning
confidence: 98%
“…A possible explanation is that reflux might implant tumor cells into the ureteral stump [2]. Thus, a history of bladder cancer is considered a high risk factor in developing ureteral stump carcinomas [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation suspicion is important and other diagnostic tool such as CT or retrograde ureterography can be helpful [9]. Nagatsuma, K. et al [1] suggested the ureteral stump must be correctly evaluated using retrograde ureterography in any patient with hematuria in the follow-up period after nephrectomy for RCC. In our case, the intravenous urography did not show any evidence of abnormality in right residual urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the remaining ureteral stump does not receive routine examination during follow-up. Nagatsuma, K. et al [1] reported a male patient presented with microscopic hematuria during a routine checkup after undergoing a radical nephrectomy for RCC. The histologic diagnosis of the patient was transitional carcinoma of the ureteral stump.…”
Section: Introductionmentioning
confidence: 99%